Numerical study of heat transfer of embossed plate fined heat sink - Mohamed Ali, Suliman Mohamed; Faris, Waleed Fekry; Ismail, Ahmad Faris (IOP Publishing Ltd., 2017)
In this article, a study of the thermal performance of embossed fined mini-channel heat sink numerically has been carried out using CFD. Commercial software STAR-CCM+ was used for the investigation. Embossed impressions were vertical to the heat sink base. The numerical results were presented in terms of flow visualization,a temperature distribution on the heat sink, velocity contour, and streamlines, Nusselt number for heat supply ranging from 18 to 70.4 W under natural convection. The existence of artificial geometry on the fin surface leads to greater Nusselt number due to the high energy fluid flow mixing near the heat sink wall by the separation and reattachment of the boundary layer. In addition, an embossed heat sink has shown better temperature distribution. The result showed a good agreement with available experimental data.